Sirtfood intake in relation to the 10-year risk of major adverse cardiovascular events: a population-based cohort study - Mahdieh Golzarand; Saghar Estaki; Parvin Mirmiran; Fereidoun Azizi (Nutrition & Metabolism, 2024)
Abstract Background Sirtuins have an important role in the regulation of metabolic and biological processess. Thus, we hypothesized that foods that could activate sirtuins, known as “sirtfood”, may improve health status. So, this study was aimed at investigating the association between the amount of sirtfood intake and the risk of major adverse cardiovascular events (MACE). Methods In this cohort study, 2918 adults who had no history of MACE at the start of the study (2006–2008) participated and were followed up on until 2018. The amount of sirtfoods intake (servings per week) was computed using a validated food frequency questionnaire. Each patient’s medical records were evaluated to detect MACE. The Cox proportional hazards model was applied to assess the association between the amount of sirtfood intake and the risk of MACE. Results The median duration of the study was 10.6 years. The hazard ratio (HR) for the risk of MACE was 0.70 for the second (95% CI: 0.50, 0.98) and 0.60 (95% CI: 0.42, 0.86) for the third tertile of sirtfoods intake compared with the first tertile. This association was nonlinear, and sirtfoods consumption of more than five servings per week did not result in a lower risk of MACE. In addition, there was a significant interaction between age (P-interaction < 0.001) and sirtfoods intake in relation to MACE occurrence. When assessing sirtfood components, compared with the lowest intake, the highest amount of soy (HR: 0.74, 95% CI: 0.56, 0.99) and parsley (HR: 0.62, 95% CI: 0.47, 0.83) intake was related to a lower risk of MACE. Conclusion Our results indicated an inverse association between a higher amount of sirtfood intake and a lower risk of MACE incidents. This association was nonlinear, and having more than five servings of sirtfood per week did not reduce the risk of MACE any further.